2010
DOI: 10.2337/db10-0542
|View full text |Cite
|
Sign up to set email alerts
|

Congenic Mesenchymal Stem Cell Therapy Reverses Hyperglycemia in Experimental Type 1 Diabetes

Abstract: OBJECTIVEA number of clinical trials are underway to test whether mesenchymal stem cells (MSCs) are effective in treating various diseases, including type 1 diabetes. Although this cell therapy holds great promise, the optimal source of MSCs has yet to be determined with respect to major histocompatibility complex matching. Here, we examine this question by testing the ability of congenic MSCs, obtained from the NOR mouse strain, to reverse recent-onset type 1 diabetes in NOD mice, as well as determine the imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
119
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(127 citation statements)
references
References 52 publications
6
119
0
2
Order By: Relevance
“…In co-culture experiments, conditioned DCs induced a higher frequency of T cells with a regulatory phenotype and increased T cell secretion of anti-inflammatory IL-10 and TGF-β and IL-6 molecules. Therefore, an amplifying loop that mediates and propagates immunomodulation while inhibiting the maturation of inflammatory DCs can be envisaged [19]. Although data regarding the effects on beta cell function and survival remain controversial [45,46], IL-6 may also stimulate beta cell repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In co-culture experiments, conditioned DCs induced a higher frequency of T cells with a regulatory phenotype and increased T cell secretion of anti-inflammatory IL-10 and TGF-β and IL-6 molecules. Therefore, an amplifying loop that mediates and propagates immunomodulation while inhibiting the maturation of inflammatory DCs can be envisaged [19]. Although data regarding the effects on beta cell function and survival remain controversial [45,46], IL-6 may also stimulate beta cell repair.…”
Section: Discussionmentioning
confidence: 99%
“…In NOD mice, MSC-released IL-6 has been reported to affect DC phenotype, differentiation and cytokine production and to divert the CD11c + subset toward a more regulatory tolerogenic phenotype [19]. Studies on the co-transplantation of allogenic islets and MSCs in streptozotocin-induced diabetic mice have shown that downregulation of the maturation, co-stimulatory and MHC class II molecules of recipient DCs contributes to graft survival by conversion to a more tolerogenic phenotype [20].…”
Section: Introductionmentioning
confidence: 99%
“…MSCs can be expanded ex vivo and have in a number of studies in animal models of type 1 diabetes been forwarded as an attractive therapy to ameliorate or reverse manifest diabetes (15)(16)(17). Besides having systemic immunomodulatory properties, the MSCs have been observed to specifically home to the damaged islets and to local pancreatic lymph nodes.…”
mentioning
confidence: 99%
“…On the other hand, most studies have shown beneficial effects of cellular and cytokine interventions on islet remodeling and recovery from injury without significant conversion to produce insulin (8,12,19,33,39,40,42,45,66,68).…”
Section: Introductionmentioning
confidence: 99%
“…The first mechanism involves direct and indirect support of revascularization and neovascularization, which has been demonstrated for whole bone marrow cells (BMCs) (8,19,39,64), adherent BMC subsets (39,40,45), lineagenegative (lin − ) (19,47), and c-kit + lin − progenitors (19). The second mechanism involves local immunomodulation attained by MSCs (7,33,40,42), and one or multiple BMC infusions (6,19). Combined vascular and immunogenic activities have been also achieved by bone marrow activation with 5-fluorouracil (8), mobilization (64), and cotransplantation (43).…”
Section: Introductionmentioning
confidence: 99%